Language Learning: Enhancing Students’ Pronunciation through English Songs - Mikhael Misa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study examines how well English songs may be used as a teaching technique to improve eighth-grade students' pronunciation. The study aims to provide evidence-based insights applicable to English as a Foreign Language (EFL) contexts and future teaching practices by methodically examining the effects of incorporating English songs into the instructional process to improve pronunciation using a Classroom Action Research (CAR) design. A methodical framework for using English songs as a teaching tool for pronunciation enhancement is created during the planning stage. Data is collected throughout the observation period to evaluate the overall efficacy of the intervention as well as the pronunciation development of the pupils. Throughout iterative cycles, this data becomes the basis for evaluating and improving instructional tactics. Results and debates regarding using songs to teach pronunciation are presented in the study. Songs improve pronunciation and make learning more enjoyable and pleasurable when used as an instructional technique. This method is a valuable supplement to language teaching approaches since it may increase students' motivation and self-assurance in their English-speaking skills.